Tolerance Formation for Children in Multi-religious Families at Pamekasan Avalokitesvara Temple Complex: Multicultural Islamic Education Perspectives - Ach. Sayyi; Afandi Afandi; Shahibul Muttaqien Al-Manduriy (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
Disputes and different views among the nation's children are often displayed and tend to disintegrate, primarily if this is related to the identity of each group, such as the identity of beliefs in religion, which is always used to break and bring down opponents. It must be realized that religious differences are sunnatullah, which must be practiced in social interaction by respecting each other and recognizing the existence of other religions without blaming and criticizing one another. This study aims to reveal efforts to form tolerance in children from multi-religious families in the Avalokitesvara Pamekasan Vihara complex. This study used a phenomenology-based qualitative approach. The research data were obtained through participatory observation, in-depth interviews, and document studies. The research data were then analyzed using the Spreadly model through domain, taxonomy, component, and theme analysis. The study results show that the formation of an attitude of tolerance in children from the perspective of multicultural Islamic education is carried out through habituation, example, guidance, and advice. Parents in multi-religious families, through their efforts to, adjust themselves to social reality.